2017
DOI: 10.1007/s40119-017-0092-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Circulating PCSK9 Concentrations Predict Subclinical Atherosclerotic Changes in Low Risk Obese and Non-Obese Patients

Abstract: IntroductionMany studies have highlighted the important role of PCSK9 in the development of cardiometabolic changes and its possible function as a biomarker of myocardial infarction or ischemic heart disease. This study aimed to determine the relationship between circulating PCSK9 levels and subclinical vascular changes in the group of low risk patients without manifest cardiovascular diseases.MethodsIn this study, 120 healthy patients, free of manifest cardiovascular diseases, diabetes mellitus, and without l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
3
15
0
2
Order By: Relevance
“…One such example was our observation that circulating proprotein convertase subtilisin/kexin type 9 (PCSK9) levels were positively correlated with BMI, as well as tracked with weight loss. This extends prior smaller studies where PCSK9 has been positively associated with obesity cross-sectionally 27,28 , and is particularly notable in light of the known role of PCSK9 levels in LDL cholesterol metabolism and atherosclerosis development [29][30][31] . Another interesting observation is that elevated AXL Receptor Tyrosine Kinase (AXL) levels among obese individuals decreased upon weight loss.…”
Section: Discussionsupporting
confidence: 80%
“…One such example was our observation that circulating proprotein convertase subtilisin/kexin type 9 (PCSK9) levels were positively correlated with BMI, as well as tracked with weight loss. This extends prior smaller studies where PCSK9 has been positively associated with obesity cross-sectionally 27,28 , and is particularly notable in light of the known role of PCSK9 levels in LDL cholesterol metabolism and atherosclerosis development [29][30][31] . Another interesting observation is that elevated AXL Receptor Tyrosine Kinase (AXL) levels among obese individuals decreased upon weight loss.…”
Section: Discussionsupporting
confidence: 80%
“…The concentrations of PCSK9 in adipose tissue positively correlated with BMI values, the most used clinical index of adiposity. Interestingly, PCSK9 plasma concentrations were also related to carotid artery intima-media thickness (cIMT) in overweight and obese individuals, in comparison with the normal weight group, suggesting that PCSK9 could be an indicator as well as a player of cardiometabolic and vascular changes induced by excessive adiposity [31].…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to determine the serum PCSK9 concentrations at different degrees of subclinical atherosclerosis and then to compare them with the subclinical inflammation measured by the hsCRP. In our previous study [14], we found that there was a significant correlation between the PCSK9 concentrations and elevated BMI values. This study also indicated that the weight gain was related to elevated circulating levels of PCSK9.…”
Section: Discussionmentioning
confidence: 67%
“…From this study, we excluded those patients with one or more of the exclusion criteria: patients undergoing a lipidlowering therapy or patients not meeting the minimum period of three months of discontinuation of therapy, lipid profile outside the inclusion criteria and secondary cause of dyslipidaemia, manifested CV diseases (such as ischaemic heart diseases, etc. ), patients with diabetes mellitus, acute infection or chronic inflammatory diseases, significant dietary or lifestyle changes in the period shorter than six months based on the protocol of our parallel study [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation